Analogous detection of circulating tumor cells using the AccuCyte®—CyteFinder® system and ISET system in patients with locally advanced and metastatic prostate cancer. Issue 4 (29th December 2017) - van der Toom, Emma E.; Groot, Vincent P.; Glavaris, Stephanie A.; Gemenetzis, Georgios; Chalfin, Heather J.; Wood, Laura D.; Wolfgang, Christopher L.; de la Rosette, Jean J.M.C.H.; de Reijke, Theo M.; Pienta, Kenneth J.
Abstract : Introduction: Circulating tumor cells (CTCs) can provide important information on patient's prognosis and treatment efficacy. Currently, a plethora of methods is available for the detection of these rare cells. We compared the outcomes of two of those methods to enumerate and characterize CTCs in patients with locally advanced and metastatic prostate cancer (PCa). First, the selection‐free AccuCyte ® − CyteFinder ® system (RareCyte ®, Inc., Seattle, WA) and second, the ISET system (Rarecells Diagnostics, France), a CTC detection method based on cell size‐exclusion. Methods: Peripheral blood samples were obtained from 15 patients with metastatic PCa and processed in parallel, using both methods according to manufacturer's protocol. CTCs were identified by immunofluorescence, using commercially available antibodies to pancytokeratin (PanCK), EpCAM, CD45/CD66b/CD34/CD11b/CD14 (AccuCyte ® − CyteFinder ® system), and pancytokeratin, vimentin (Vim) and CD45 (ISET system). Results: The median CTC count was 5 CTCs/7.5 mL (range, 0‐20) for the AccuCyte ® − CyteFinder ® system and 37 CTCs/7.5 mL (range, 8‐139) for the ISET system ( P  < 0.001). Total CTC counts obtained for the two methods were correlated ( r  = 0.750, P  = 0.001). When separating the total CTC count obtained with the ISET system in PanCK+/Vim− and PanCK+/Vim+ CTCs, the total CTC count obtained with the AccuCyte ® − CyteFinder ® system was moderately correlated with the PanCK+/Vim− CTCs, and strongly correlated with the PanCK+/Vim+ CTCs ( r  = 0.700, P  = 0.004 and r  = 0.810, P  < 0.001, respectively). Conclusion: Our results highlight significant disparities in the enumeration and phenotype of CTCs detected by both techniques. Although the median amount of CTCs/7.5 mL differed significantly, total CTC counts of both methods were strongly correlated. For future studies, a more uniform approach to the isolation and definition of CTCs based on immunofluorescent stains is needed to provide reproducible results that can be correlated with clinical outcomes.